Exploring the Symbiotic Link: Co-Integration Analysis of the Egyptian Stock Exchange and International Equity Markets - Tawfik Azrak; Omar Alaeddin (Shirkah: Journal of Economics and Business, 2024)
The present study addresses the limited discussion on the equity market in the Middle East and North African region (MENA) concerning the spill-over effects from international equity markets. By employing time series techniques, we examine the integration and causality of interdependencies among five major stock exchange markets worldwide: USA, UK, Malaysia, Hong Kong, and Japan, along with their relationship with the Egypt Stock Exchange market. Spanning from March 1998 to January 2018, our study uniquely considers the interaction between developed and developing countries. Our co-integration findings reveal the limitations of international diversification for investors with long holding periods. We highlight the importance of seeking non-co-integrated markets, such as Malaysia and Hong Kong, which were found to be insignificant in this study, for investors aiming to diversify their portfolios and explore interesting long and short-term investment opportunities.